2021
DOI: 10.1177/20503121211000919
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 on health workers in Ghana: A multicentre, cross-sectional study

Abstract: Introduction: The COVID-19 pandemic has exacted an appreciable burden on health systems globally including adverse psychological impacts on health workers. This study sought to assess COVID-19-related fear, depression, anxiety and stress among hospital staff, potential factors that may help reduce its psychological effects and their personal coping strategies. The study will help to highlight the psychological impact of COVID-19 on Ghanaian health workers and indirectly serve as a needs assessment survey for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 50 publications
3
66
2
1
Order By: Relevance
“…HPs in Jordan faced the highest level of anxiety, in Canada the highest level of stress, and in Egypt the highest level of insomnia. The reverse scenarios (lowest estimates) were found for depression and anxiety in South Korea, for stress in Ghana, and for insomnia in Greece [28] (Table 3). The psychological tools that measured the highest pooled prevalence of depression of 47.02% using 9 studies [2,31,46,53,57,65,85,87,90], anxiety of 58.06% using 9 studies [2,31,46,53,57,65,85,87,90], stress of 69.46% using 5 studies [24,69,86,100,103], and insomnia of 46.58% using 16 studies [8,24,27,32,33,50,53,54,56,60,86,88,90,91,95] were HADS, HADS, PSS and ISI respectively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…HPs in Jordan faced the highest level of anxiety, in Canada the highest level of stress, and in Egypt the highest level of insomnia. The reverse scenarios (lowest estimates) were found for depression and anxiety in South Korea, for stress in Ghana, and for insomnia in Greece [28] (Table 3). The psychological tools that measured the highest pooled prevalence of depression of 47.02% using 9 studies [2,31,46,53,57,65,85,87,90], anxiety of 58.06% using 9 studies [2,31,46,53,57,65,85,87,90], stress of 69.46% using 5 studies [24,69,86,100,103], and insomnia of 46.58% using 16 studies [8,24,27,32,33,50,53,54,56,60,86,88,90,91,95] were HADS, HADS, PSS and ISI respectively.…”
Section: Discussionmentioning
confidence: 96%
“…the characteristics of the selected studies[2,8,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68, 69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90, 91,92,93,94,95,96,97,98,99,100,101,102,103,104], 30 of which were from China, 6 from Italy, 6 from India, 4 from the United States, 3 from each of Pakistan and Iran, 2 from…”
mentioning
confidence: 99%
“…The rapid infectivity of the coronavirus however unsettled the health systems with a high proportion of infected patients requiring hospitalization [ 7 ]. The pandemic also affected HIV/ART services as several studies reported negative psychological effects on healthcare workers [ 8 , 9 ], decline in clinic attendance [ 10 ], and challenges organising services within facilities [ 11 ] which further impacted uptake and delivery of ART services.…”
Section: Introductionmentioning
confidence: 99%
“…Nania et al [2] also posited that adolescents' quest to understand the reasons behind social stratifications in their societies induce the feeling of anxiety and worry in them especially when they belong to the disadvantaged end of the spectrum. Psychological distresses are more prevalent among the young adult category (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and the older adult group (above 60 years) [3]. Vahedian-Azimi and others further explained that access to diversified information on social media incubates anxiety and some sense of worry among young adults whereas depression, which is induced by loneliness and regret, is common among people within the older age group.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the few available studies were conducted in other jurisdictions outside of Ghana. The only known research on COVID-19 and psychological distress in Ghana was conducted by Ofori et al [27] to highlight the psychological impact of COVID-19 on Ghanaian health workers and indirectly serve as a needs assessment survey for input to support affected staff and the broader health system. Against this background, this study seeks to examine psychological distress among adults in Ghana in light of the pandemic.…”
Section: Introductionmentioning
confidence: 99%